Penerapan Hukuman Terhadap Pelaku Tindak Pidana Pembunuhan Hubungan Keluarga (Studi Kasus Nomor, 593/Pid.B/2012/PN.Psp) - Samsir Alam; Sarmadan Pohan (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The purpose of this research is to find out which factors are the occurrence of a family crime and to find out which is the basis for the Judge's determination to determine the guilt of the defendant in the crime of murder related to family. The research method that the author uses in writing this research is normative research using secondary data sources and in the form of legislation. Collecting techniques, namely Interview (Interview), Documentation Study and also study the files that have been archived in Padangsidimpuan District Court which will then be analyzed by Induction and Deduction. The conclusion in this study that the factors that lead to the murder of family relationships is caused by disputes between the accused and the victim where disputes include the issue of children and the problem of disharmony between the defendant and the victim and that the basis for consideration by the Judge to determine mistakes the defendant in the crime of murder of family relations is by proving the chronology of the murder by confessing the defendant in court.Key words: Victims of Narcotics Abuse; Criminal Prison; Rehabilitation.